Obesity prevention in child care: A review of U.S. state regulations - Slining Meghan; Walker Elizabeth M; Cradock Angie; Benjamin Sara E; Gillman Matthew W (BMC, 2008)
ABSTRACT Objective To describe and contrast individual state nutrition and physical activity regulations related to childhood obesity for child care centers and family child care homes in the United States. Methods We conducted a review of regulations for child care facilities for all 50 states and the District of Columbia. We examined state regulations and recorded key nutrition and physical activity items that may contribute to childhood obesity. Items included in this review were: 1) Water is freely available; 2) Sugar-sweetened beverages are limited; 3) Foods of low nutritional value are limited; 4) Children are not forced to eat; 5) Food is not used as a reward; 6) Support is provided for breastfeeding and provision of breast milk; 7) Screen time is limited; and 8) Physical activity is required daily. Results Considerable variation exists among state nutrition and physical activity regulations related to obesity. Tennessee had six of the eight regulations for child care centers, and Delaware, Georgia, Indiana, and Nevada had five of the eight regulations. Conversely, the District of Columbia, Idaho, Nebraska and Washington had none of the eight regulations. For family child care homes, Georgia and Nevada had five of the eight regulations; Arizona, Mississippi, North Carolina, Oregon, Tennessee, Texas, Vermont, and West Virginia had four of the eight regulations. California, the District of Columbia, Idaho, Iowa, Kansas, and Nebraska did not have any of the regulations related to obesity for family child care homes. Conclusion Many states lack specific nutrition and physical activity regulations related to childhood obesity for child care facilities. If widely implemented, enhancing state regulations could help address the obesity epidemic in young children in the United States.